Microbowls with Controlled Concavity for Accurate Microscale Mass Spectrometry (Adv. Mater. 12/2022). Issue 12 (24th March 2022) - Xu, Linfeng; Li, Xiangpeng; Li, Wenzong; Chang, Kai‐chun; Yang, Hyunjun; Tao, Nannan; Zhang, Pengfei; Payne, Emory M.; Modavi, Cyrus; Humphries, Jacqueline; Lu, Chia‐Wei; Abate, Adam R.
Abstract : Patterned Surfaces Patterned surfaces can enhance the sensitivity of laser desorption ionization mass spectrometry by segregating and concentrating analytes, but their fabrication is challenging. In article number 2108194, Adam R. Abate and co‐workers introduce a simple method to pattern substrates with micrometer‐scale wells yielding more‐sensitive mass spectrometry measurements compared to flat‐surface or cylindrical wells. The wells also concentrate and localize cells and beads for cell‐based assays.